How do auditors follow rules? - Lau, Yeng Wai (Global Academic Excellence, 2021)
Motivated by concerns about whether rules and regulations capture the rich complexity of auditing and auditors follow rules and regulations to the extent of compromising judgment, this paper provides a synthesis of the literature in the field of auditing and psychology to better understand how auditors follow rules in exercising judgment. Five testable propositions are derived. A model of rules compliance is also developed to better understand auditors’ practices and performance. The model sheds light on how auditors comply or conform to rules given the nature of audit tasks, ranging from well-structured to illstructured. While the model is developed in the context of audit judgment, the model is also applicable in other similar judgmental settings with a range of well and ill-structured tasks. The propositions and model developed in this study serve as a platform for future empirical research in auditing as well as other similar domains of expertise.